Investigation of the EATS Feeding Assessment as an Outcome Measure: A Case Series - Blair Carsone; Bryce Smith (World Nutrition, 2025)
Pediatric feeding difficulties can be categorized as developmental, motor-based, sensory-based, or behavioral. Sensory-based feeding difficulties result from dysfunctional responses to mealtime stimuli. The Environment, Attitudes, Temperament, and Sensory (EATS) Feeding Assessment is a caregiver questionnaire designed to assess sensory-based feeding difficulties and factors related to feeding performance. This report outlines the fourth phase of research, determining if the EATS Feeding Assessment can be used as an outcome measure. Data were collected at baseline and at six-month follow-up following standard outpatient occupational therapy treatment for sensory-based feeding difficulties. Quantitative scores from the attitudes, temperament, and sensory sections were compared, excluding the qualitative environment section. Standard care for treatment included sensory strategies, caregiver education, environmental modification, and fine motor coordination. At follow-up, all three children demonstrated improvements in temperament and sensory scores. Two children had improvements in attitudes scores while one had no change. The EATS Feeding Assessment should now undergo